Utilization of a multi-sectoral approach in strengthening cross-sectoral referrals of survivors of sexual violence from the health sector in Kenya - Agesa, Carolyne Ajema (Department of Public Health and Family Medicine, 2020)
Background: Sexual violence policy frameworks and service delivery models are well defined in Kenya. However, little is known about the extent to which different sectors effectively work together to ensure survivors receive comprehensive care. The need for a multi-sectoral response framework has been cited in the literature. Nonetheless, it is not clearly defined what this entails in the Kenyan context. Aim: This thesis aimed at reviewing and documenting the processes involved in the delivery of services by the different sectors with a focus on patient flow, data systems, community perceptions and referral mechanisms The study also aimed to develop an in-depth understanding of the factors that influence reporting of cases of sexual violence, provision of services and uptake of available services. Also explored were the requisites for a coordinated and multi-sectoral approach to sexual violence. Methods: This is a cross-sectional study that applied a mixed-methods approach. Qualitative interviews were conducted with 23 service providers, survivors and caregivers. The quantitative component entailed abstraction of service statistics from records maintained for survivors. A total of 1259 records were obtained from two hospitals, two police stations and two courts in two counties in Kenya. Key informant guides were used for the qualitative interviews, while an Excel data abstraction tool was implemented to capture data obtained from service statistics. Thematic analysis of qualitative data was undertaken using NVivo 12. The records were analysed using SPSS Version 20.0 The Anderson model (1973) informed the interpretation of the qualitative data. Data were triangulated during the analysis across the interviews and service records. Findings: Defilement constitute the largest proportion of cases of sexual violence reported across different sectors. Poor quality of sexual violence data maintained for survivors across different service delivery points presents a difficulty in tracking survivors to examine completeness in service uptake. Existent difficulties persist in determining the extent to which the different sectors are responsive to the survivor's need for quality and comprehensive services. Survivors--more so female and children--do not have autonomy in decision making regarding whether to report a sexual violation meted on them or not. Lack of a standardized multi-sectoral referral framework contributes to survivor frustration in accessing services due to the multiple referral pathways, costs and time delays involved. There is continued reliance on informal community level arbitration of cases despite the existing legal provisions in the Sexual Offences Act. Conclusion: The Anderson (1973) framework provides a basis for an in-depth understanding of survivors' service utilization related behaviours and decisions. The findings reveal the interconnectedness of predisposing enabling and need factors in the context of the available services and decision making on what service to take up. While the health sector and police continue to play a key role in response to sexual violence, there still exist gaps that impede the comprehensiveness in response. Communities still prefer reaching out to informal sources of support. However, there is a disconnect between formal and informal sources of support. The need for a multi-sectoral and coordinated approach to sexual violence is critical, and its design should be informed by the needs of survivors. Measures should be put in place to address enabling factors to service access through training of providers on the management of survivors. This study provides anecdotal evidence to be utilized in informing development and implementation of multi-sectoral models of post-sexual violence service delivery models in Kenya and in Sub-Saharan Africa.